Honor in the face of shame: the semiotics of the American flag at political-sex-scandal press conferences. Issue 3 (2nd July 2016) - Mandell, Hinda; Martin, Kelly Norris
Abstract: Political sex scandals occurred in rapid succession from 2004 to 2011 in the U.S. The press conferences that followed received significant interest from the national press and public. Interestingly, a general pattern occurred where politicians who resigned at the press conference displayed an American flag and wore a lapel pin, while those who remained in office did not. After conducting a semiotic analysis of eight popular-press images, we argue that the absence of the American flag indicates a separation of personal scandal from the office, and the presence of the flag indicates that personal transgression has public consequences as embodied by the politician's resignation. Furthermore, the politician's desire for control over his public representation may inversely impact his concern for social presence and media richness in the U.S. Removal of the visual presence (lower media richness) will also have an impact on the visual literacy or the holistic nature of the event's visual language. After all, an audience's understanding of that event is largely accomplished through available visuals, such as the American flag.